Patient expectations of fair complaint handling in hospitals: empirical data - Sluijs Emmy M; Friele Roland D (BMC, 2006)
Abstract Background A common finding in several studies is patients' dissatisfaction with complaint handling in health care. The reasons why are for the greater part unknown. The key to an answer may be found in a better understanding of patients' expectations. We investigated patients' expectations of complaint handling in hospitals. Methods Subjects were patients who had lodged a complaint at the complaint committees of 74 hospitals in the Netherlands. A total of 424 patients (response 75%) completed a written questionnaire at the start of the complaint procedures. Derived from justice theory, we asked what they expected from fair procedures, fair communication and fair outcome of complaint handling. Results The predominant reason for complainants to lodge a complaint was to prevent the incident from happening again. Complainants expected fair procedures from the complaint committee, in particular an impartial position. This was most important to 87% of the complainants. They also expected to be treated respectfully. Furthermore, they expected the hospital and the professional involved to respond to their complaint. A change in hospital performances was the most wanted outcome of complaint handling, according to 79% of the complainants. They also expected disclosure from the professionals. Professionals should admit a mistake when it had occurred. More complainants (65%) considered it most important to get an explanation than an apology (41%). Only 32% of complainants expected the professional to make an effort to restore the doctor-patient relationship. A minority of complainants (7%) wanted financial compensation. Conclusion Nearly all complainants want to prevent the incident from happening again, not out of pure altruism, but in order to restore their sense of justice. We conclude that complaint handling that does not allow for change is unlikely to meet patients' expectations. Secondly, complaint handling should not be left exclusively to complaint committees, the responses of hospital and professionals are indispensable.